Uncertainty, trust and formal governance mechanism in Indonesian family SMEs - K Kussudyarsana; Muhammad Halim Maimun; S Soepatini (Diponegoro International Journal of Business, 2019)
This paper discusses the relationship between uncertainty, trust and the application of formal governance mechanism in Indonesian family SMEs. The data were obtained through survey to 360 family firms in indonesia. This study used factor analysis to validate the construct and multiple regression analysis to examine the hypothesis. The moderation testing indicated that trust moderated the relationship between uncertainty and formal governance was negatively significant